2004
DOI: 10.1103/physreve.69.061307
|View full text |Cite
|
Sign up to set email alerts
|

Fluctuations of the solid discharge of gravity-driven particle flows in a turbulent stream

Abstract: Substantial variations in the particle flux are commonly observed in field measurements on gravel-bed rivers and in laboratory experiments mimicking river behavior on a smaller scale. These fluctuations can be explained by the natural variability of sediment supply and hydraulic conditions. We conducted laboratory experiments of particle transport down a two-dimensional inclined channel, for which the boundary conditions were properly controlled. Most flow variables and the features of particle trajectories we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
46
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(49 citation statements)
references
References 14 publications
3
46
0
Order By: Relevance
“…If the existence of an incision threshold i > c were to be confirmed, it would mean that this value should be taken into account in models of river incision instead of the critical Shields number c . This is also consistent with the possible existence of an energy threshold necessary to effectively erode a small volume of material at impact, as observed by Bitter (1963).…”
Section: The Role Of Sediment Supply Shields Number and Bed Roughnesupporting
confidence: 74%
See 1 more Smart Citation
“…If the existence of an incision threshold i > c were to be confirmed, it would mean that this value should be taken into account in models of river incision instead of the critical Shields number c . This is also consistent with the possible existence of an energy threshold necessary to effectively erode a small volume of material at impact, as observed by Bitter (1963).…”
Section: The Role Of Sediment Supply Shields Number and Bed Roughnesupporting
confidence: 74%
“…The bedload flux then reaches a relatively steady value: from this moment we consider that the system is in the permanent regime. Let us note that we still observe relatively large fluctuations of the bedload flux, consistent with what has been observed experimentally (see, for instance, Böhm et al, 2004, andAncey et al, 2006), and which motivated stochastic approaches to bedload transport on top of a sediment layer ( Roseberry et al, 2012;Ancey and Heyman, 2014;Fan et al, 2014). However, we will not investigate these fluctuations in further detail and in the rest of the discussion all results are computed in the permanent regime and only concern the average values of the sediment and energy fluxes.…”
Section: Sediment Transportsupporting
confidence: 48%
“…Indeed, Böhm et al (2004) showed that even 23 under well-controlled experimental conditions and despite steady supply, solid discharge 24 exhibits significant variations with time. One explanation given by the writers was thecollective entrainment of deposited particles, which was observed during our own 1 experiments.…”
mentioning
confidence: 99%
“…Experiments were carried out in a tilted, narrow, glasssided channel, 2 m in length, already used in previous studies (Bigillon 2001;Ancey et al 2002;Böhm et al 2004). Figure 1 shows a sketch of the experimental facility.…”
Section: Experimental Facilities and Proceduresmentioning
confidence: 99%
“…Initially, the trajectory of a single saltating or rolling bead was analyzed (Ancey et al 2002(Ancey et al , 2003. The channel was then supplied continuously with beads, and measurements were taken at transport equilibrium over the mobile bed (Böhm et al 2004;Böhm 2005). All particle trajectories were calculated by image processing ) allowing analysis of the fluctuations of sediment rates as well as the state of movement (rolling or saltation).…”
Section: Introductionmentioning
confidence: 99%